2008
DOI: 10.1002/cncr.23239
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells infiltrating human nonsmall‐cell lung cancer are enriched in CD56brightCD16 cells and display an impaired capability to kill tumor cells

Abstract: BACKGROUND. Despite natural killer (NK) cells being originally identified and named because of their ability to kill tumor cells in vitro, only limited information is available on NK cells infiltrating malignant tumors, especially in humans. METHODS. NK cells infiltrating human nonsmall cell lung cancers (NSCLC) were analyzed with the aim of identifying their potential protective role in an antitumor immune response. Both relevant molecule expression and functions of NK cells infiltrating NSCLC were analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
289
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 332 publications
(326 citation statements)
references
References 51 publications
(70 reference statements)
29
289
2
2
Order By: Relevance
“…Recently, we have described that an endogenously activated pleural fluid NK (PF-NK) population is a major source of IFN-g in response to Mtb [10,11]. Consistently, PF-NK are enriched in CD56 bright cells, as has been observed in other chronic inflammatory sites [12,13] or in tumor-affected tissues [14]. Together with the classical NK functions (i.e.…”
Section: Introductionsupporting
confidence: 54%
“…Recently, we have described that an endogenously activated pleural fluid NK (PF-NK) population is a major source of IFN-g in response to Mtb [10,11]. Consistently, PF-NK are enriched in CD56 bright cells, as has been observed in other chronic inflammatory sites [12,13] or in tumor-affected tissues [14]. Together with the classical NK functions (i.e.…”
Section: Introductionsupporting
confidence: 54%
“…We have previously shown that a CD3 neg CD56 þ NKp44 þ cell population selectively infiltrates NSCLC, whereas it is virtually undetectable in normal lung tissues 42 . In addition, NCR þ cells are mainly localized in the tumour stroma, in particular within stromal regions characterized by high density of lymphocytes 42 .…”
Section: Resultsmentioning
confidence: 98%
“…We have previously shown that a CD3 neg CD56 þ NKp44 þ cell population selectively infiltrates NSCLC, whereas it is virtually undetectable in normal lung tissues 42 . In addition, NCR þ cells are mainly localized in the tumour stroma, in particular within stromal regions characterized by high density of lymphocytes 42 . As NCR þ ILC3 express high levels of NKp44, these data prompted us to further investigate whether the various ILC subsets, and in particular Group 3 ILC expressing NCRs, were present in the tumour microenvironment.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…33,34 Similar changes and dysfunction were reported in NK cells isolated from patients with esophageal squamous cell carcinoma and non-small cell lung carcinoma, particularly in pleural effusion. 38,39 The downregulation of CD16 on NK cells has been shown to be driven by TGFβ and leads to conversion from cytotoxic to a more immunoregulatory phenotype similar to decidual NK cells. 30,38 In the current study, we found that NK cells downregulated their CD16 expression upon exposure to ovarian tumor microenvironment but this conversion was mitigated by PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%